(untitled) (Latakia University Journal -Basic Sciences Series, 2019)
In this paper, we aim to find a set of analytical soliton wave solutions for the time fractional generalized Fitzhugh - Nagumo Equation with constant coefficients, in the sense of modified Riemann - Liouville fractional derivative, by using the exp- function method. Comparing the results with these of classical form of the time fractional Fitzhugh - Nagumo equation. We found that this method is effective and easy to apply for this type of partial fractional nonlinear differential equations.